Assessment of Husbands’ Knowledge on Antenatal Care in a Tertiary Care Hospital, Karachi: Husbands’ Knowledge on Antenatal Care - Ahmed, Mansoor; Ali Siddiqui, Danish; Mirani, Naseer Ahmed; Khan, Danish Ahmed; Siddiqui, Faraz; Din, Nadeem Ud (Pakistan Journal of Health Sciences, 2024)
The husband’s involvement during pregnancy was considered very disappointing earlier. As a result, women did not inform their husbands about their troubles and concerns during pregnancy. In some cases, the severity of complications leads to the death of the fetus and mother. However, with time, husbands now take responsibility for their wives during pregnancy and antenatal care. The involvement of husbands in antenatal care visits reduces the risk of maternal mortality. Objective: To evaluate the level of knowledge regarding antenatal care among husbands of pregnant women attending a tertiary care hospital in Karachi. Methods: A cross-sectional research design was selected and conducted with 360 husbands who accompanied their wives for the antenatal services at the Outpatient Gynecology and Obstetrics Department of Dow University of Health Sciences (DUHS) Ojha Campus Karachi. The study questionnaire comprised twenty questions about the husband’s knowledge of antenatal care. Data were analyzed by using SPSS version 21.0. Results: The study findings showed that (57.5%) husbands felt that antenatal care was valuable, the majority of the husbands (95.6%) felt that it was not necessary to go for antenatal care if there was no complication, and (32.2%) husbands were considered to believe that a minimum of three antenatal visits were enough for the care. More than half were aware of the danger signs of pregnancy, and they knew that a pregnant woman should deliver her baby in the health care facility. Conclusions: The current research study concluded that a large number of husbands felt that antenatal care was valuable, but still a lack of knowledge was found in different antenatal care components. There was a need for awareness of all the components of antenatal care among husbands of pregnant women.